Wenshen-Jianpi prescription, a Chinese herbal medicine, improves visceral hypersensitivity in a rat model of IBS-D by regulating the MEK/ERK signal pathway - Jiang, Tianyuan; Niu, Ran; Liu, Qian; Fu, Yuhan; Luo, Xiaoying; Zhang, Tao; Wu, Baoqi; Han, Juan; Yang, Yang; Su, Xiaolan; Chen, Jiande D. Z.; Song, Gengqing; et al. (Frontiers in Pharmacology, 2022)
The goal of the study was to analyze whether WJP can alleviate visceral hypersensitivity in IBS-D model rats. In this study, 36 Sprague–Dawley (SD) rats aged 4 weeks old were randomly divided into two groups: the model group (n = 27) and the control group (n = 9). The rat model of IBS-D was established by modified compound methods for 4 weeks. After the modification, IBS-D rats were randomly divided into three groups, namely, the IBS-D model group (n = 9), the positive drug group (n = 9), and the WJP group (n = 9), with different interventions, respectively. The control group was fed and allowed to drink water routinely. The Bristol stool scale scores were used to assess the severity of diarrhea. Abdominal withdrawal reflex (AWR) scores were used to assess visceral sensitivity. Expression of TNF-α was measured, and histopathological examinations were performed to assess colon inflammation in IBS-D model rats. Key factors of the MEK/ERK signal pathway in the tissue of the colon and hippocampus were measured to analyze the mechanism of WJP. Compared with the control group, the Bristol stool scale scores in the model group were significantly increased (p < 0.0001). The scores of the WJP group were significantly decreased compared with the model group (p = 0.0001). Compared with the control group, AWR scores in the model group at each pressure level were significantly increased (p = 0.0003, p < 0.0001, p = 0.0007, and p = 0.0009). AWR scores of the WJP group were significantly decreased compared with the model group (p = 0.0003, p = 0.0007, p = 0.0007, and p = 0.0009). Compared with the control group, the model group had significantly higher expression of TNF-α in the colon tissue (p < 0.0001). However, the WJP group had significantly lower level of TNF-α compared with the model group (p < 0.0001). Meanwhile, compared with the control group, the relative expression of the proteins of p-MEK1/2, p-ERK1, and p-ERK2 in the colon tissue was significantly increased in the model group (p < 0.0001). Compared with the model group, the relative expression of the proteins in the colon tissue were significantly decreased in the WJP group (p < 0.0001, p = 0.0019, and p = 0.0013). Compared with the control group, the relative expression of the proteins of p-MEK1/2, p-ERK1, and p-ERK2 in the hippocampus tissue were significantly increased in the model group (p < 0.0001). Compared with the model group, the relative expression of the proteins in the hippocampus tissue were significantly decreased in the WJP group (p = 0.0126, p = 0.0291, and p = 0.0145). The results indicated that WJP can alleviate visceral hypersensitivity in IBS-D model rats, possibly mediated by downregulating the expression of TNF-α, p-MEK1/2, p-ERK1, and p-ERK2 in the colon tissue. At the same time, WJP also affects downregulating the expression of p-MEK1/2, p-ERK1, and p-ERK2 in the hippocampus tissue.